Multilayer weather-resistant adhesive film and application method thereof
Through the design of multi-layer weather-resistant adhesive films, the problems of insufficient durability and adhesion of existing metal anti-corrosion technology under complex environmental conditions are solved, achieving efficient anti-corrosion and weather resistance of metal plates, and reducing construction costs. Cost and time.
Patent Information
- Application Number
- CN202411413517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
AI Technical Summary
When facing complex environmental conditions, existing metal anti-corrosion technology lacks durability and adhesion, and consumes a lot of manpower and material resources during construction, which is costly.
Multi -layer of weather adverivation membrane, including metal adhesive layer, intermediate transition layer, and the outer layer. Through specific materials and hierarchical design, the antifegial corrosion, weather resistance and adhesion of the adhesive membrane are enhanced.
The effective anti -corrosion, weather resistance and good adhesion of metal boards have been realized, reducing construction costs and time, and improving engineering efficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal plate protective films, and more particularly, to a multi-layer weather-resistant adhesive film and an application method thereof. Background Art
[0002] In modern industry and construction, metal materials are widely used in various structural parts and equipment due to their excellent mechanical strength, processing performance and durability. For example, metal materials such as steel and aluminum alloys are widely used in building frames, mechanical equipment, and transportation vehicles. However, metal materials are prone to corrosion and aging when exposed to air, moisture, salt and other corrosive media for a long time, which in turn affects their service life and safety. Therefore, how to effectively protect the metal surface and extend its service life has become an important issue in the engineering field.
[0003] Traditional anti-corrosion technologies usually include coating treatment, electroplating, spraying, hot-dip plating and other methods. These technologies can provide protection for metal surfaces to a certain extent, but their durability and adhesion are often insufficient when facing complex environmental conditions. For example, although coating treatment can form a protective film on the metal surface, when environmental factors such as ultraviolet radiation, temperature changes, humidity fluctuations, etc. act on the coating, the coating is prone to peeling, cracking or corrosion penetration. In addition, although electroplating can provide better anti-corrosion performance, it is costly, the construction process is complicated, and it will cause certain pollution to the environment in some applications.
[0004] With the increasing requirements for energy saving and environmental protection in the industrial field, the urgency of developing new anti-corrosion materials and processes is increasing. In this context, the emergence of TPO (thermoplastic polyolefin) waterproofing membranes provides a new solution for metal anti-corrosion. TPO waterproofing membranes are increasingly valued by the construction and industrial sectors due to their excellent weather resistance, UV resistance and good chemical stability. Especially when combined with metal materials, TPO membranes can be bonded in different ways to improve the anti-corrosion performance of metals.
[0005] However, the existing TPO waterproofing membrane also has some shortcomings in the application process. For example, the common practice is to stick butyl glue on the top of the layer and then stick the steel plate, or use epoxy glue to stick the steel plate on the layer. Although these methods can achieve a certain anti-corrosion effect, they require a lot of manpower and material costs during the construction process. The use of butyl glue and epoxy glue not only increases the material cost, but also has certain requirements for construction technology and construction environment, resulting in a long construction period and affecting project efficiency. In addition, the traditional glue bonding method may also lead to insufficient bonding strength due to factors such as temperature and humidity in some cases, thereby affecting the overall anti-corrosion effect. Summary of the invention
[0006] In view of the problems existing in the prior art, the present application provides a multi-layer weather-resistant adhesive film and an application method thereof.
[0007] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0008] The metal bonding layer includes ethylene acrylic acid copolymer; the intermediate transition layer includes octene and propylene multi-component blend; and the outer surface layer includes polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0009] Furthermore, the thickness of the metal bonding layer accounts for 5% to 45% of the thickness of the adhesive film layer.
[0010] Furthermore, the thickness of the intermediate transition layer accounts for 20% to 60% of the thickness of the adhesive film layer.
[0011] Furthermore, the thickness of the outer layer accounts for 20% to 60% of the thickness of the adhesive film layer.
[0012] The multi-layer anticorrosion and weather-resistant adhesive film for metal plates of the present invention realizes corrosion protection, weather resistance and good adhesion to metal plates through multi-layer structural design and selection of specific materials. The adhesive film is composed of a metal adhesive layer, an intermediate transition layer and an outer surface layer. The combination of these three layers not only enhances the overall physical properties, but also ensures close adhesion between the adhesive film and the metal plate.
[0013] First, the metal bonding layer is designed to achieve a strong bond between the adhesive film and the metal plate. The selected material is ethylene acrylic acid copolymer (EAA), which has excellent bonding properties, especially its ability to form chemical bonds on the metal surface, which significantly improves the bonding strength. The structure of ethylene acrylic acid copolymer has zwitterionic properties, which can form strong ionic bonds with metal ions to ensure long-lasting adhesion between the metal and the adhesive film. In addition, EAA material has good processability and can achieve efficient bonding at low temperatures, which means that the bonding strength between the adhesive film and the metal can still be guaranteed under different processing conditions.
[0014] Next, the intermediate transition layer is composed of a multi-component blend of octene and propylene. This layer acts as a buffer layer to adjust the stress distribution between the metal bonding layer and the outer surface layer, while providing additional bonding capacity. This multi-component blend was selected based on its chemical compatibility and excellent mechanical properties. The combination of octene and propylene gives the material a certain elasticity and impact resistance, which can effectively absorb and disperse the stress caused by external factors (such as temperature changes, mechanical shocks, etc.), thereby extending the service life of the adhesive film.
[0015] Finally, the outer layer is a polyolefin resin (TPO) prepared by blending ethylene propylene rubber (EPDM) and polypropylene (PP). EPDM has excellent ozone resistance, aging resistance and chemical corrosion resistance, while polypropylene provides good mechanical strength and impact resistance. This outer layer can not only effectively prevent the invasion of external corrosive media, but also resist aging problems caused by long-term exposure to sunlight and adverse weather conditions. The thickness of the outer layer is controlled between 20% and 60% of the thickness of the adhesive film layer. This ratio ensures that the outer layer will not be too thick to affect the flexibility and ductility of the entire film while providing protection.
[0016] Furthermore, the metal bonding layer, the intermediate transition layer and the outer surface layer also include porous phase change particles accounting for 0.5% to 3% of the total content of the components of the layer.
[0017] Furthermore, the porous phase-change particles contain nano-magnetic ferrosoferric oxide.
[0018] Furthermore, the metal bonding layer contains porous phase-change particles accounting for 1.3% to 1.4% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.5% to 0.7% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 2.5% to 3% of the total content of the components of the layer.
[0019] The metal bonding layer, the intermediate transition layer and the outer layer all contain a certain amount of porous phase change particles, and the proportion of these porous phase change particles varies according to the functional requirements of different levels. The role of the porous phase change particles is to store and release heat through the phase change of tetradecane, thereby adjusting the temperature distribution of the bonding film. The content of porous phase change particles in the metal bonding layer and the outer layer is higher than that in the intermediate transition layer, which makes the direct bonding between the bonding layer and the metal more stable and firm. In the metal bonding layer, the particle content is set to 1.3% to 1.4%. This ratio can fully exert the phase change characteristics of the porous phase change particles and will not have a negative impact on the adhesion performance of the bonding layer. The appropriate amount of phase change particles can effectively regulate the heat between the metal and the adhesive film, reduce the stress concentration caused by temperature changes, and enhance the long-term stability of the bonding layer. The particle content of the intermediate transition layer is relatively low (0.5% to 0.7%). The purpose of this design is to maintain the flexibility and stress buffering performance of the transition layer. As an intermediate layer connecting the metal bonding layer and the outer layer, the main function of the transition layer is to absorb and disperse stress from the outside, so it needs to maintain a certain elasticity and deformation capacity. Too high a particle content may cause the material to be too rigid, thus losing its stress buffering effect. The outer layer, as a protective layer directly exposed to the environment, has the highest particle content (2.5% to 3%). This high content design helps to improve the weather resistance and aging resistance of the outer layer. The main task of the outer layer is to resist environmental erosion such as ultraviolet rays, moisture, and oxygen. Therefore, after introducing a higher content of porous phase change particles, the outer layer can more effectively absorb and dissipate external heat, avoiding material aging due to drastic changes in ambient temperature.
[0020] Secondly, porous phase change particles also have a certain strengthening effect, especially in an environment subjected to mechanical stress. These particles increase the internal porosity of the adhesive film through their pore structure, which can effectively buffer mechanical impact and slow down the propagation of cracks.
[0021] Furthermore, the preparation method of the porous phase change particles is as follows:
[0022] Step A1: adding nanoparticles and polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the polysulfone is dissolved; wherein the weight proportions of the components are: 10-12 parts of polysulfone, 40-45 parts of N,N-dimethylacetamide, 40-45 parts of diethylene glycol, 1-2 parts of nanoparticles, and 8-10 parts of tetradecane; the nanoparticles include nano-silicon dioxide and nano-magnetic ferroferric oxide in a mass ratio of 1:2-5;
[0023] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0024] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0025] Furthermore, the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the metal bonding layer is 1:3-4; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the intermediate transition layer is 1:2-2.5; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the outer layer is 1:3-4.
[0026] The porous phase change particles are prepared by the above-mentioned preparation method. In addition to the tetradecane material contained in the particles as phase change energy storage, the surface of the particles has a large number of microporous structures. This is because the polysulfone particles have a complex porous structure after curing through the selection and control of temperature and solvent. On the one hand, this porous structure increases the internal porosity of the adhesive film through its pore structure, which can effectively buffer mechanical impact and slow down the propagation of cracks; on the other hand, the microporous structure of these particles can give the adhesive film a certain hydrophobicity, so that the adhesive film has better weather resistance and anti-fouling effect.
[0027] In the metal bonding layer, the mass ratio of nano-silicon dioxide and nano-iron tetroxide in the porous phase change particles is 1:3-4. The purpose of this ratio design is to improve the magnetic response performance of the bonding layer. A higher content of nano-iron tetroxide can enhance the magnetism of the metal bonding layer, so that it can be more firmly bonded to the metal plate under the action of the magnetic field. This magnetic bonding method further improves the bonding strength, which is especially suitable for scenes with high bonding requirements for metal materials. The appropriate addition of nano-silicon dioxide ensures the thermal stability and mechanical strength of the bonding layer, so that it still has good bonding performance under high temperature conditions. In the intermediate transition layer, the ratio of nano-silicon dioxide and nano-iron tetroxide is 1:2-2.5. This design mainly considers the flexibility and stress buffering performance of the transition layer. The main function of the intermediate layer is to absorb external impact and stress distribution. The appropriate amount of nano-iron tetroxide improves the thermal conductivity and magnetic response of the transition layer, so that it can work better with the adjacent layers. Nano-silicon dioxide prevents the film layer from failing due to excessive stress by improving the mechanical strength and thermal stability of the material, thereby ensuring the durability of the entire multilayer structure. In the outer layer, the ratio of nano-silicon dioxide to nano-ferroferric oxide is 1:3-4. Similar to the metal bonding layer, the higher content of nano-ferroferric oxide is mainly used to improve the anti-magnetic and weather resistance of the outer layer. The outer layer is directly exposed to the environment, especially in magnetic fields and high temperature environments. The higher content of nano-ferroferric oxide can enhance the response to external heat and magnetic fields, while improving corrosion resistance. The addition of nano-silicon dioxide ensures that the outer layer still has good mechanical properties in extreme weather and resists external impact and wear.
[0028] The invention discloses an application method of a multi-layer weather-resistant adhesive film, wherein the multi-layer anticorrosive weather-resistant adhesive film is bonded to a metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.
[0029] In summary, the present invention has the following beneficial effects:
[0030] The multi-layer weather-resistant adhesive film of the present invention has excellent performance with its unique design and material selection, especially in terms of corrosion protection, weather resistance and adhesion of metal plates. The film is composed of three parts: a metal bonding layer, an intermediate transition layer and an outer surface layer. The interaction and coordination between the layers enable it to play a good effect under different environmental conditions.
[0031] The metal bonding layer uses ethylene acrylic acid copolymer (EAA), which has excellent bonding properties and the ability to form strong chemical bonds on the metal surface, ensuring a strong bond between the film layer and the metal plate. In addition, the zwitterionic properties of EAA enable it to effectively form ionic bonds with metal ions, further improving the bonding strength. The intermediate transition layer is composed of a multi-component blend of octene and propylene, which mainly plays a buffering role, adjusts the stress distribution between the upper and lower layers, and provides additional bonding capacity. The elasticity and impact resistance of this layer of material enable it to absorb the stress caused by external impact and temperature changes, significantly extending the service life of the adhesive film. Its thickness accounts for 20% to 60% of the film layer, ensuring that sufficient buffering capacity is provided without affecting flexibility. The outer layer is a polyolefin resin made of ethylene propylene rubber and polypropylene, which has excellent ozone resistance, aging resistance and chemical corrosion resistance. The thickness of this layer is also controlled between 20% and 60%, ensuring that it does not affect the flexibility of the film while providing protection. The outer layer effectively prevents the intrusion of external corrosive media, while resisting aging problems caused by ultraviolet rays and harsh weather conditions, ensuring long-term stable performance.
[0032] The further introduction of porous phase change particles, especially the use of nano-magnetic ferroferric oxide, provides additional thermal management and enhancement for the membrane layer. The content of particles at different levels is designed reasonably, so that the high proportion of particles in the metal bonding layer and the outer layer enhances the bonding strength and weather resistance, while the relatively low proportion in the intermediate transition layer ensures its flexibility and cushioning performance. These particles store and release heat through phase change, optimize temperature distribution, reduce stress concentration caused by temperature changes, and improve the long-term stability and durability of the membrane.
[0033] In summary, the multi-layer weather-resistant adhesive film has significantly improved its performance in corrosion resistance, weather resistance and bonding through hierarchical design and clever material selection. It has broad application prospects, especially in the field of metal material bonding with high requirements. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] Example 1
[0036] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0037] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0038] The thickness of the metal bonding layer accounts for 5% of the thickness of the adhesive film layer.
[0039] The thickness of the intermediate transition layer accounts for 60% of the thickness of the adhesive film layer.
[0040] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0041] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0042] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0043] Example 2
[0044] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0045] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0046] The thickness of the metal bonding layer accounts for 45% of the thickness of the adhesive film layer.
[0047] The thickness of the intermediate transition layer accounts for 30% of the thickness of the adhesive film layer.
[0048] The thickness of the outer layer accounts for 25% of the thickness of the adhesive film layer.
[0049] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0050] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0051] Example 3
[0052] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0053] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0054] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0055] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0056] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0057] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0058] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0059] Example 4
[0060] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0061] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0062] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0063] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0064] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0065] The metal bonding layer, the intermediate transition layer and the outer surface layer also include porous phase-change particles accounting for 2% of the total content of the components of the layer.
[0066] The preparation method of porous phase change particles is as follows:
[0067] Step A1: adding polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of the components are: 10 parts of polysulfone, 40 parts of N,N-dimethylacetamide, 40 parts of diethylene glycol, and 8 parts of tetradecane;
[0068] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0069] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0070] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0071] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0072] Example 5
[0073] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0074] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0075] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0076] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0077] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0078] The metal bonding layer, the intermediate transition layer and the outer surface layer also include porous phase-change particles accounting for 3% of the total content of the components of the layer.
[0079] The preparation method of porous phase change particles is as follows:
[0080] Step A1: adding polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of the components are: 12 parts of polysulfone, 45 parts of N,N-dimethylacetamide, 45 parts of diethylene glycol, and 10 parts of tetradecane;
[0081] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0082] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0083] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0084] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0085] Example 6
[0086] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0087] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0088] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0089] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0090] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0091] The metal bonding layer, the intermediate transition layer and the outer surface layer also include porous phase-change particles accounting for 0.5% of the total content of the components of the layer.
[0092] The preparation method of porous phase change particles is as follows:
[0093] Step A1: adding polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of the components are: 11 parts of polysulfone, 43 parts of N,N-dimethylacetamide, 42 parts of diethylene glycol, and 9 parts of tetradecane;
[0094] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0095] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0096] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0097] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0098] Example 7
[0099] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0100] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0101] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0102] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0103] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0104] The metal bonding layer contains porous phase-change particles accounting for 1.3% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.5% of the total content of the components of the layer; and the outer surface layer contains porous phase-change particles accounting for 2.5% of the total content of the components of the layer.
[0105] The preparation method of porous phase change particles is as follows:
[0106] Step A1: adding polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of the components are: 11 parts of polysulfone, 43 parts of N,N-dimethylacetamide, 42 parts of diethylene glycol, and 9 parts of tetradecane;
[0107] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0108] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0109] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0110] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0111] Example 8
[0112] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0113] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0114] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0115] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0116] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0117] The metal bonding layer contains porous phase-change particles accounting for 1.6% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.8% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 3% of the total content of the components of the layer.
[0118] The preparation method of porous phase change particles is as follows:
[0119] Step A1: adding polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of the components are: 11 parts of polysulfone, 43 parts of N,N-dimethylacetamide, 42 parts of diethylene glycol, and 9 parts of tetradecane;
[0120] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0121] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0122] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0123] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0124] Example 9
[0125] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0126] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0127] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0128] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0129] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0130] The metal bonding layer contains porous phase-change particles accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.6% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 2.7% of the total content of the components of the layer.
[0131] The preparation method of porous phase change particles is as follows:
[0132] Step A1: adding polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of the components are: 11 parts of polysulfone, 43 parts of N,N-dimethylacetamide, 42 parts of diethylene glycol, and 9 parts of tetradecane;
[0133] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0134] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0135] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0136] A method for applying a multi-layer weather-resistant adhesive film is to heat-press it onto the surface of a metal plate.
[0137] Example 10
[0138] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0139] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0140] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0141] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0142] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0143] The metal bonding layer contains porous phase-change particles accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.6% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 2.7% of the total content of the components of the layer.
[0144] The preparation method of porous phase change particles is as follows:
[0145] Step A1: adding nanoparticles and polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of each component are: 12 parts of polysulfone, 45 parts of N,N-dimethylacetamide, 45 parts of diethylene glycol, 2 parts of nanoparticles, and 10 parts of tetradecane; the nanoparticles include nano-silicon dioxide and nano-magnetic ferroferric oxide in a mass ratio of 1:2-5; (wherein the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the metal bonding layer is 1:3; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the intermediate transition layer is 1:2; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the outer layer is 1:3.)
[0146] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0147] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0148] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0149] The invention discloses an application method of a multi-layer weather-resistant adhesive film, wherein the multi-layer anticorrosive weather-resistant adhesive film is bonded to a metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.
[0150] Embodiment 11
[0151] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0152] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0153] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0154] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0155] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0156] The metal bonding layer contains porous phase-change particles accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.6% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 2.7% of the total content of the components of the layer.
[0157] The porous phase change particles have paraffin as the core material and melamine resin as the wall material.
[0158] The method for preparing porous phase change particles comprises the following steps:
[0159] Step A1: adding nanoparticles and polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of each component are: 12 parts of polysulfone, 45 parts of N,N-dimethylacetamide, 45 parts of diethylene glycol, 2 parts of nanoparticles, and 10 parts of tetradecane; the nanoparticles include nano-silicon dioxide and nano-magnetic ferroferric oxide in a mass ratio of 1:2-5; (wherein the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the metal bonding layer is 1:4; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the intermediate transition layer is 1:2.5; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the outer layer is 1:4.)
[0160] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0161] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0162] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0163] The invention discloses an application method of a multi-layer weather-resistant adhesive film, wherein the multi-layer anticorrosive weather-resistant adhesive film is bonded to a metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.
[0164] Example 12
[0165] A multi-layer weather-resistant adhesive film, comprising a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer;
[0166] The metal bonding layer comprises ethylene acrylic acid copolymer; the intermediate transition layer comprises octene and propylene multi-component blend; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene.
[0167] The thickness of the metal bonding layer accounts for 25% of the thickness of the adhesive film layer.
[0168] The thickness of the intermediate transition layer accounts for 40% of the thickness of the adhesive film layer.
[0169] The thickness of the outer layer accounts for 35% of the thickness of the adhesive film layer.
[0170] The metal bonding layer contains porous phase-change particles accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.6% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 2.7% of the total content of the components of the layer.
[0171] The porous phase change particles have paraffin as the core material and melamine resin as the wall material.
[0172] The method for preparing porous phase change particles comprises the following steps:
[0173] Step A1: adding nanoparticles and polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the dissolution; wherein the weight proportions of each component are: 12 parts of polysulfone, 45 parts of N,N-dimethylacetamide, 45 parts of diethylene glycol, 2 parts of nanoparticles, and 10 parts of tetradecane; the nanoparticles include nano-silicon dioxide and nano-magnetic ferroferric oxide in a mass ratio of 1:2-5; (wherein the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the metal bonding layer is 1:3.5; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the intermediate transition layer is 1:2.3; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the outer layer is 1:3.8.)
[0174] Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min;
[0175] Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
[0176] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.
[0177] The invention discloses an application method of a multi-layer weather-resistant adhesive film, wherein the multi-layer anticorrosive weather-resistant adhesive film is bonded to a metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.
[0178] Comparative Example
[0179] In Comparative Example 1, epoxy glue was used to bond the TPO layer to the surface of the metal plate.
[0180] Detection Methods
[0181] The adhesive films of Examples 1-12 were bonded to the steel plate, and the TPO layer of Comparative Example 1 was bonded to the surface of the steel plate with epoxy glue to obtain Example and Comparative Example samples. Subsequently, a xenon lamp aging test for 10,000 hours was performed, and the same batch of Example and Comparative Example samples were first exposed to outdoor sunlight for 6 months and then subjected to a xenon lamp aging test for 20,000 hours. The test results are shown in Table 1 below.
[0182] The contact angles of the samples of the embodiments and comparative examples were measured using a contact angle tester.
[0183] Table 1
[0184]
[0185] The above test results show that the adhesive film of the present invention is easy to construct and has good weather resistance. The weather resistance and hydrophobicity of the adhesive film are significantly improved by adding porous phase change particles and doping nano silicon dioxide and nano magnetic ferroferric oxide into the porous phase change particles.
[0186] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A multi-layer weather-resistant adhesive film, characterized in that: It includes a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer; The metal bonding layer includes ethylene acrylic acid copolymer; the intermediate transition layer includes octene and propylene multi-component blend; and the outer surface layer includes polyolefin resin prepared from ethylene propylene rubber and polypropylene.
2. The multi-layer weather-resistant adhesive film according to claim 1, characterized in that: The thickness of the metal bonding layer accounts for 5% to 45% of the thickness of the adhesive film layer.
3. The multi-layer weather-resistant adhesive film according to claim 2, characterized in that: The thickness of the intermediate transition layer accounts for 20% to 60% of the thickness of the adhesive film layer.
4. The multi-layer weather-resistant adhesive film according to claim 3, characterized in that: The thickness of the outer layer accounts for 20% to 60% of the thickness of the adhesive film layer.
5. The multi-layer weather-resistant adhesive film according to claim 1, characterized in that: The metal bonding layer, the intermediate transition layer and the outer surface layer also include porous phase-change particles accounting for 0.5% to 3% of the total content of the components of the layer.
6. The multi-layer weather-resistant adhesive film according to claim 5, characterized in that: The porous phase-change particles contain nano-magnetic ferroferric oxide.
7. The multi-layer weather-resistant adhesive film according to claim 5, characterized in that: The metal bonding layer contains porous phase-change particles accounting for 1.3% to 1.4% of the total content of the components of the layer; the intermediate transition layer contains porous phase-change particles accounting for 0.5% to 0.7% of the total content of the components of the layer; and the outer layer contains porous phase-change particles accounting for 2.5% to 3% of the total content of the components of the layer.
8. The multi-layer weather-resistant adhesive film according to claim 1, characterized in that: The preparation method of the porous phase-change particles is as follows: Step A1: adding nanoparticles and polysulfone to a solution of N,N-dimethylacetamide and diethylene glycol mixed in proportion, adding tetradecane after the polysulfone is completely dissolved, and obtaining an oil phase after the polysulfone is dissolved; wherein the weight proportions of the components are: 10-12 parts of polysulfone, 40-45 parts of N,N-dimethylacetamide, 40-45 parts of diethylene glycol, 1-2 parts of nanoparticles, and 8-10 parts of tetradecane; the nanoparticles include nano-silicon dioxide and nano-magnetic ferroferric oxide in a mass ratio of 1:2-5; Step A2: dripping the oil phase into the water phase, the water phase is a polyvinyl alcohol solution with a mass concentration of 1%, the mass ratio of the oil phase to the water phase is 1:10, and the temperature of the polyvinyl alcohol solution is controlled to be 70° C., and the polyvinyl alcohol solution is stirred at a speed of 1000 r / min; Step A3: After standing, remove the supernatant and soak the obtained particles in 50% mass concentration ethanol. Change the soaking solution every 12 hours. After changing and washing at least 3 times, dry at room temperature.
9. The multi-layer weather-resistant adhesive film according to claim 1, characterized in that: The mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the metal bonding layer is 1:3-4; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the intermediate transition layer is 1:2-2.5; the mass ratio of nano-silicon dioxide and nano-magnetic ferroferric oxide in the porous phase-change particles added to the outer surface layer is 1:3-4.
10. A method for applying the multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to any one of claims 1 to 9, characterized in that: The multi-layer anti-corrosion and weather-resistant adhesive film is bonded to the metal plate by heat pressing and applying a magnetic field to one side of the metal plate.